Comparative the effect of using locally collected premix with some imported premixes in some productive characteristics of broilers (Ross 308). - Lazim, Jamel S.; Abbas, Riyadh S. (Journal of Kerbala for Agricultural Sciences, 2017)
The experiment was carried out in the poultry field of the Department of Animal Production Techniques at the Technical College of Musayyib for the period from 1/11/2016 to 5/12/2016, in order to study the effect of the premix, most of which were collected locally and compared with imported feed mixtures in some production characteristics, in this study, 240 one day old chicks Rose 308 was used The chicks were randomly distributed in to four equal experimental treatments , 60 chicks divided into two replicates (30 chicks . replicate-1) using 2.5% of the locally premix (T1) and compared with three premixes Wafi (T2), provimi (T3) and Max Care (T4), mixing and equipping the mixtures with their premixes to cover the requirements of the birds according to the Rose guide, which followed four stages of life (pre-starter from 1 - 10 days , starter from 11 - 20 days , grower from 21 - 30 days and finisher 31 – until Marketing), and using a ready-program, modern software (BEST MIX, 2016), version 3.03 of Cargil, the US company to make this premix, as well as when the installation of all 16 rations. The results of the production characteristics of body weight, weight gain, feed consumption, and feed conversion rasio showed the possibility of using the premix of additives locally collected for the absence of significant differences in the cumulative rate of the studied traits between all the treatments.